Information System Quality Assessment Methods - Korn, Alexandra; Svatá, Vlasta, 1952-; Blahanravau, Yauheni; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2015)
This thesis explores challenging topic of information system quality assessment and mainly process assessment. In this work the term Information System Quality is defined as well as different approaches in a quality definition for different domains of information systems are outlined. Main methods of process assessment are overviewed and their relationships are described. Process assessment methods are divided into two categories: ISO standards and best practices. The main objective of this work is application of gained theoretical knowledge in process assessment with CobiT 4.1 and CobiT 5.0 frameworks, and comparing results. The objective was achieved through consultation with processes owner and the completed questionnaires filled in by management of OnLine S.r.l. Additionally targeted level of capability in CobiT 5.0 is compared with actual, achieved level.
Vedoucí práce: Vlasta Svatá
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: informační management [obor dipl. práce]; diplomové práce; master's theses